HUBUNGAN MOTIVASI DENGAN KINERJA KARYAWAN PADA PRIME PARK HOTEL PEKANBARU - Syahsudarmi, Siti (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was conducted at Prime Park Hotel Pekanbaru which is located at Jl. Jendral Sudirman Blok. A No. 3 - 6, Simpang Tiga, Pekanbaru and aims to determine the influence of motivation on employee performance at Prime Park Hotel Pekanbaru. The population in this study were 58 respondents. Based on the discussion with simple linear regression, the resulting regression equation is Y = 12,329 + 1,122 X, a constant of 12,329 indicates that if the independent variable X (work motivation) is 0, then the dependent variable Y (performance) is 12,329. While the regression coefficient of variable X (work motivation) is 1.122, indicating that if the work motivation has increased by 1 point, the performance will also increase by 1.122. The coefficient is positive, meaning that there is a positive relationship between work motivation and performance, the more work motivation increases, the performance will also increase. Work motivation has an effect on employee performance based on the results of the t test because the value of tcount> ttable (12.783> 2.00324) means that Ho is rejected, meaning that there is a significant influence between work motivation on performance. So it can be concluded that work motivation has a significant effect on performance. The value of R Square is 0.745 or 74.5%. This shows that the percentage of the contribution of the independent variable (work motivation) to the dependent variable (performance) is 74.5%. While the remaining 25.5% is influenced by other variables not included in this study.